Geographic Information Systen (GIS) Mapping of Toddler Cases Stunting Cases in Bantul Regency in 2022: Pemetaan Sistem Informasi Geografis (Sig) Kasus Balita Stunting Di Wilayah Kabupaten Bantul Tahun 2022 - Sari, Ana Dewi Lukita; Rohman, Hendra; Salsabila, Amalia (Universitas Muhammadiyah Sidoarjo, 2025)
Geographic information system GIS is technology based on computers to collect, analyze, and serve data and information from an object that is connected and located on the ground. A toddler with stunted is shorter than his or her age, less than the -2 standard of the World Health Organization’s WHO growth curve. A condition caused by lack of nutritional intake in a toddler during the first 1000 days of life. This study aimed to map the cases of a stunted toddler in the Bantul district with Quantum of GIS and analyze the influencing factors based on specific nutritional interventions. Varieties of qualitative research with planned case studies. The subjects sample were nutrition officers of the Bantul Public Health Office while the subjects sample were three stunted toddlers in the Kapanewon district of Bantul. Data collection for toddlers with stunted was using ePPBGM electronic Nutrition Report Based on Sleep Record. In 2022, there were 3,001 cases of developmental delay in toddlers. The three higher-ranked cases in Kapanewon are Kapanewon Imogiri 492, Dlingo 258, and Piyungan 228. Risk factors of stunting in toddlers through specific nutritional interventions. The conclusion: 1. We can see that the higher toddler case mappings of the three Kapanewons have clearer visuals compared with the other Kapanewons. 2. The analysis of incidents Stunted a toddler from the higher three kapanewons through specific nutritional interventions where available in Imogiri Kapanewon, the mom does not want to do IMD, give exclusive breastfeeding, pregnant with KeK anemia, Pregnant women with anemia and parenting patterns are still high compared with Dlingo and Piyungan Kapanewon. Suggestion: Stunting is a complex problem as of specific nutritional interventions and sensitive nutritional interventions are needed.